A nine months follow-up study of hemodynamic effect on bioabsorbable coronary stent implantation - Lan, Yisha (2020)
Coronary artery disease has emerged as one of the major diseases causing death worldwide. Coronary stent has great effect to improve blood flow to the myocardium subtended by that artery, in which bioresorbable vascular scaffolds are new-generation stents used by people. However, Coronary stents implantation has a risk of restenosis, which is relative to hemodynamic parameters. Most of existing literatures studied in this issue have not taken into account such important factors as the strut thickness and lumen profile, and has yet to analyze the time effects among hemodynamic parameters over a certain period of time based on individual models. In this research, we proposed a framework to assess the chronic impact of hemodynamic on coronary stent implantation. In the framework, the optical coherence tomography (OCT) is combined with angiography to reconstruct patient-specific models of bioresorbable vascular scaffolds. Then, the hemodynamics parameters are extracted through the simulated 3D models, obtaining the distribution of wall shear stress (WSS), relative residence time (RRT) and oscillatory shear index (OSI). Finally, the changes of these parameters representing the effectiveness of hemodynamics exerted on the implanted stent can be assessed to estimate the chronic impacts. By a 9-month follow-up case study, it is observed that the difference of hemodynamic parameters are not significance. Both at baseline and 9-month follow-up experiments show that the hemodynamic parameters remain normal and similar, proving that the coronary stent implantation nowadays appears to have a robust and everlasting curative effect.